PERSEPSI DAN PARTISIPASI MASYARAKAT TERHADAP SUMBER DAYA HUTAN (Studi Kasus Tahura Bukit Barisan, Kawasan Hutan Sibayak II, Kabupaten Karo) - Rena Novelia Damanik; Oding Affandi; Liliek Pudji Asmono (Program studi Kehutanan USU, 2014)
Tahura Bukit Barisan has good variety potentials to be developed. However, Tahura Bukit Barisan’s management can not get maximal result if the rate of human’s perception and participation haven’t been known yet. Whereas, the rate of people’s perception and participation in existing can be base for UPT Tahura Bukit Barisan manager to empower community, so that they will be more active in managing and using forest potency. So, the rate of community perception and participation of Tahura Bukit Barisan have to been known. Sampling technique uses purposive sampling. This research uses primer and secondary data. Primer data collected from survey and direct interview by quisioner. Then, counted the rate of community perception and participation by using formula, then it will be grouped into three categories namely high, medium and low. The result showed the level of peoples in Dolat Rayat, Jarang Uda and Merdeka Village are grouped into good perception, but rate of community participation for some activities such as planning, actuating, and evaluation are low.Keyword : Tahura Bukit Barisan, Perception, Participation